Digital Sport Culture and Body Exposure: A Sharia Perspective on Self-Presentation in Social Media - Febriyani, Febriyani; Ibrohim, Syahid Makdum; Hasanuddin, Hasanuddin; Nurhaidah, Siti Nuri; Irfan, Ahmad; Apriyanto, Anto (Jurnal El-Thawalib, 2026)
The rapid development of the digital era has transformed the meaning of sports from a health-oriented activity into a form of self-representation within virtual spaces. This shift is reflected in the increasing prevalence of fitness-related content on social media, which not only showcases physical activities but also promotes body exposure as a visual strategy to attract attention and gain social recognition. From an Islamic perspective, such practices potentially conflict with the concept of ‘awrah and the ethical values governing bodily modesty in public spaces. This study aims to analyze the phenomenon of body exposure in digital sports through the framework of maqashid al-sharia and to formulate ethical guidelines for social media engagement in accordance with Islamic principles. The research employs a qualitative approach using library research, with primary sources derived from the Qur’an, hadith, and classical as well as contemporary Islamic jurisprudential works, particularly those of al-Nawawi, al-Qardhawi and Wahbah al-Zuhaili, complemented by secondary data from academic journals and media reports. Data analysis is conducted using a descriptive-analytical method with normative and maqashid-based approaches. The findings indicate that the transformation of digital sports has led to the commodification of the body and triggered psychological impacts such as body dissatisfaction. Within the maqashid al-sharia framework, body exposure may violate the fundamental objectives of preserving religion (hifzh al-din), life (hifzh al-nafs), and honor (hifzh al-‘irdh). Therefore, a reconstruction of sharia-based digital sports ethics is necessary, emphasizing modest dress, visual restraint, and moral awareness in social media practices to maintain a balance between digital modernity and Islamic values.